If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 3) + -7 = 4(x + -2) + 5 Reorder the terms: 3(3 + x) + -7 = 4(x + -2) + 5 (3 * 3 + x * 3) + -7 = 4(x + -2) + 5 (9 + 3x) + -7 = 4(x + -2) + 5 Reorder the terms: 9 + -7 + 3x = 4(x + -2) + 5 Combine like terms: 9 + -7 = 2 2 + 3x = 4(x + -2) + 5 Reorder the terms: 2 + 3x = 4(-2 + x) + 5 2 + 3x = (-2 * 4 + x * 4) + 5 2 + 3x = (-8 + 4x) + 5 Reorder the terms: 2 + 3x = -8 + 5 + 4x Combine like terms: -8 + 5 = -3 2 + 3x = -3 + 4x Solving 2 + 3x = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2 + 3x + -4x = -3 + 4x + -4x Combine like terms: 3x + -4x = -1x 2 + -1x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + -1x = -3 + 0 2 + -1x = -3 Add '-2' to each side of the equation. 2 + -2 + -1x = -3 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = -3 + -2 -1x = -3 + -2 Combine like terms: -3 + -2 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 6(x+13)=7x-8-3x | | 0.009x+0.2(500-x)=0.03*500 | | 3Y-2Z=-5 | | 4[x-1]=0 | | sin(3pix)=1 | | 3x(1+x)=0 | | 5x*2-7x-24=0 | | (x-3)(x-5)=64 | | (x-3)(x-5)=74 | | (x-3)(x-5)=84 | | (x+3)(x-5)=84 | | 3*x-x*log(x)=log(e^5) | | 3x-xln(x)=lne^5 | | 5x-7x-24=0 | | 4d^2-16-8d-d^2=0 | | x^3-24x^2+180x-424=0 | | 3x-xln(x)-9=(-4) | | 48=5x-28 | | 5+7x=9x-12 | | Log(x)12=5 | | y*(-3-y)=-10 | | -3y-y=-10 | | 15y-y=56 | | 3x^2-6x+1.625=0 | | f(1/2x)*(1/2x) | | 681=X+0.3X | | (0.45*1.6x)+(0.55*x)=6 | | (14/120)x(14/120)x(14/120) | | (0.45*1.6x)+(0.55*x)=3 | | 4x-9=ax-3a | | 4x-9=ax-3ax | | 4x-9=ax-3 |